Millennial-scale variations in western Sierra Nevada precipitation during the last glacial cycle MIS 4/3 transition. Issue 1 (July 2014) - Oster, Jessica L.; Montañez, Isabel P.; Mertz-Kraus, Regina; Sharp, Warren D.; Stock, Greg M.; Spero, Howard J.; Tinsley, John; Zachos, James C.
Abstract: Dansgaard–Oeschger (D–O) cycles had far-reaching effects on Northern Hemisphere and tropical climate systems during the last glacial period, yet the climatic response to D–O cycles in western North America is controversial, especially prior to 55 ka. We document changes in precipitation along the western slope of the central Sierra Nevada during early Marine Oxygen Isotope Stages (MIS) 3 and 4 (55–67 ka) from a U-series dated speleothem record from McLean's Cave. The timing of our multi-proxy geochemical dataset is coeval with D–O interstadials (15–18) and stadials, including Heinrich Event 6. The McLean's Cave stalagmite indicates warmer and drier conditions during Greenland interstadials (GISs 15–18), signified by elevated δ 18 O, δ 13 C, reflectance, and trace element concentrations, and less radiogenic 87 Sr/ 86 Sr. Our record extends evidence of a strong linkage between high-latitude warming and reduced precipitation in western North America to early MIS 3 and MIS 4. This record shows that the linkage persists in diverse global climate states, and documents the nature of the climatic response in central California to Heinrich Event 6.